The Key Technologies in Collaborative Communication for Internet of Vehicles Systems - Fu, Siyuan; Dong, Bingyi; Sun, Kaipeng (Scientific Journal of Technology, 2025)
Collaborative communication technology in the Internet of Vehicles (IoV) is a key component of intelligent transportation systems and has garnered widespread attention in recent years. It involves information sharing between vehicles, vehicles and infrastructure, vehicles and pedestrians, and vehicles and networks, aiming to enhance traffic management and optimization. With the advancement of 5G and the upcoming 6G technologies, IoV systems face demands for low latency, high reliability, and security, and the standardization process continues to deepen. Physical Layer Security (PLS) leverages channel characteristics to enhance communication confidentiality, addressing the limitations of traditional encryption techniques. Reconfigurable Intelligent Surfaces (IRS), as an emerging technology, optimize communication performance by dynamically adjusting signal reflections, particularly improving system performance in signal-degraded environments. Furthermore, resource optimization strategies, such as deep learning and algorithm optimization, further enhance the communication efficiency and reliability of IoV systems. In the future, the integration of these technologies will drive the development of IoV towards more efficient, intelligent, and secure systems.